Implementation of Iris Recognition Using Circular Hough Transform and Template Generation - Halder, AA; Pande, SR (International Journal of Computer Sciences and Engineering, 2020)
Iris recognition is considered as one of the reliable technique in biometric system to gain higher security. In this paper research is focusing on an efficient iris recognition technique. Iris of an eye image is segmented, unwrapped into a rectangular strip and normalized. Normalized iris is transformed into polar coordinate and filtered. A mask is applied for noise suppression and encoded using encoding technique. This encoded iris pattern features are extracted and template is generated. This final template is stored in the database and input image template pattern is matched using pattern matching technique. This experiment uses two standard database images CASIA V1.0 and IITD, the performance measure FAR and FRR for different threshold values is considered for the evaluation of the system.